Claiming his baby at the altar - Smart, Michelle (Harlequin presents, 2022)
"Notorious billionaire Alejandro Ramos shut Flora Hillier out of his life after their encounter nine months ago, believing she'd betrayed him. But when he learns about their child, he demands they marry--immediately. And within minutes of exchanging vows, Flora shockingly goes into labor! Ramos proves to be an excellent father, but Flora is wary of the new vulnerable feelings their whirlwind marriage exposes. Because it's one thing to trust Ramos with her body and their baby. It's a whole different thing entirely to trust him with her heart..." -- Page [4] cover.